Application of ac impedance as diagnostic tool – Low temperature electrolyte for a Li-ion battery. (1st November 2019) - Qu, Huainan; Kafle, Janak; Harris, Joshua; Zheng, Dong; Koshina, Joe; Boone, David; Drake, Alexander M.; Abegglen, Caleb J.; Qu, Deyang
Abstract: In this report, we study the impact of the solid electrolyte interphase (SEI) of lithium ion batteries (LIB) on low temperature performance in 3-electrode pouch cells with electrochemical impedance spectroscopy. Two kinds of electrolytes are used for the comparison purpose. One is chosen as the best low temperature electrolyte (1.0 M LiPF6 in ethylene carbonate (EC)/ethyl methyl carbonate (EMC)/dimethyl carbonate (DMC) at a certain ratio) developed in our laboratory by design of experiment method. The other electrolyte used is state-of-art baseline electrolyte (1.0 M LiPF6 in 3 EC/7 EMC). Electrochemical impedance of cathode, anode and the complete cell is measured in various states of aging, charge, and temperature conditions. Our results show that majority of the full cell impedance arises from anode SEI. Cathode SEI has very small impedance. Approximately 75% of full cell impedance is from anode and rest is from cathode. The impedance data are fitted by RC equivalent circuit model to extract various parameters of interfacial phenomena. Also, the data are analyzed by using the relation between the impedance, its distribution of relaxation times (DRT), and the time constants. Conclusively, the high rate performance of a LIB in low temperature depends on the kinetics of the electrochemical process rather than the value of polarization resistance.